The traits of conservative correction of congenital clubfoot at the children of the first year old - Ye. V. Chuguy; D. D. Melnik (Бюллетень сибирской медицины)
On the grounds of analysis results of the congenital clubfoot’s treatments 120 children of the first year old the indications and contraindications to correction of the deformation by the soft redressmentory bandage were determinated, the particularities of their using were distinguished. The designed method raises the good results of the conservative treatment of the disease more then on 30% in contrast with the traditional methods. The efficiency correction of the congenital clubfoot by the soft bandage straightly depends on observance particularities of the repair of the deformation by the offered way.